RANCANGAN KEBIJAKAN BUDAYA ORGANISASI UNTUK PENINGKATAN KAPABILITAS BANK SENTRAL - Widyo Gunadi; Manuntun Parulian Hutagaol; Muliaman D Hadad (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
The aim of this study is to develop policies of organization culture (OC). The policies analysis cover management process and its changing in Bank Indonesia, including direction and substance of OC, developing ideal models, methods, dynamic change and its management.  Awareness about the importance of OC in improving the performance of the organization had been recognized by management of Bank Indonesia in the surface, but when examined the dynamics of the changes, the implementation seem fluctuated. Using a system approach, this research employ three main tools: Analytical Network Process (ANP), Strategic Assumption Surfacing and Testing (SAST), and Interpretative Structural Modeling (ISM). The knowledge base data are compiled using combination of several methods: survey, focus group discussion (FGD), statistics of secondary data, and structured in depth interviews. This research has found the new values which should be adopted for BI are integrity professional, visionary, competence, and transparent. Besides, it also delevelop models to implement a new organization culture management. In terms of organization culture change program, this research uncovers several important phenomena such as: the central role of the board of governor, the function of performance management and assessment, and the role of director in every unit.Keywords : organization Culture, Values,Sub-culture Type, Analytical Network Process, Strategic Assumption Surfacing and Testing, Interpretative Structural Modeling